Combined spinal-epidural anesthesia for renal transplant in a lung transplant recipient: a case report - Bellini, Valentina; Madoni, Cristiana; Badino, Marco; Del Rio, Paolo; Iaria, Maurizio; Puliatti, Carmelo; Bignami, Elena (Acta Biomedica Atenei Parmensis, 2022)
A 67-year-old lung transplant recipient with severe comorbidities was admitted for renal transplant. As anesthesia technique, combined spinal-epidural at the T11-T12 level was chosen, associated with intravenous sedation. Graft’s function initially results altered, bringing to pulmonary fluid overload. Beginning from the postoperative day 5 there was a slow but constant gain-of-function of the graft, proven by an improvement of renal function indexes and by the resolution of the pulmonary edema.Conclusions: Whereas general anesthesia remains the gold standard anesthesia technique for kidney transplant, a locoregional anesthesia, could be a feasible and effective option in patients at high risk of respiratory complications. (www.actabiomedica.it)